Approach to data collection for soil carbon modelling in Benin - Guendehou, G.H. Sabin; Mäkipää, Raisa (Finnish Forest Research Institute, 2014)
Carbon stocks and changes in carbon stocks in forest ecosystems can be estimated either by direct measurements or using modelling approach. Given that direct measurements are expensive and time-consuming, modelling is preferred in countries with limited resources like Benin. But, in practice modelling is complemented by direct measurements in order to increase the validity of the model estimates. The objective of this technical paper is to provide guidance to collect data through direct measurements in order to improve the applicability of model-based approach to estimate soil carbon stocks and its changes in forest ecosystems. Further objective is to encourage the estimation of soil carbon pool in developing tropical countries.
Keywords: dynaamiset mallit; hiilitase; hiilivarasto; metsämaaperä; forest ecosystems; litterbag experiment; litterfall; soil modelling; soil sampling